Time Management, Daily Journaling Habit, and Gadget Utilization by High School Students - Galuh Sekar Wijayanti; Nur Azizah; Panggih Wahyu Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2023)
The use of gadgets is important to note because it greatly influences time management and student learning outcomes. Gadgets can have positive or negative effects. Therefore, it is necessary to provide assistance in the use of gadgets by students so that they have a positive impact on students' time management abilities and the quality of their learning. The purpose of this research is to find out about Time Management, Daily Journal Writing Habits, and the Use of Gadgets by High School Students. The research method used in this study is a quantitative research method with the main data collection tool in the form of a questionnaire. The questionnaire was administered to a 15% random sample from a total population of 908 high school students. The ability of students in time management was seen that there were 14.8% of students had high time management skills, 78.5% of students had moderate time management skills, and 6.7% of students had low time management skills. This condition showed that time management skills among high school students still required intensive efforts to improve. As an effort to improve time management capabilities, there are four aspects of time management: setting goals and priorities; planning and scheduling; ability to control time; and a preference for being organized. For the use of devices in making plans and activity journals, 45.8%, the remaining 54.2% did not use devices at all to make plans and activity journals. Social media was the highest activity carried out when students hold gadgets amounted of 55.9%, chat and voice calls were in second place with a considerable difference of 17.2%. Related to the widespread use of gadgets among teenagers, their use was not optimal for improving self-quality, especially for time management skills.